Management, performance, and applications of micro irrigation systems - Goyal, Megh Raj (Research advances in sustainable micro irrigation ;, 2014)
Management, Performance, and Applications of Micro Irrigation Systems, the fourth volume in the Research Advances in Sustainable Micro Irrigation series, emphasizes sustainable and meaningful methods of irrigation to counter rampant water scarcity. In many parts of the world, this scarcity significantly affects crop yield, crop quality, and, consequently, human quality of life. This important volume presents the best management practices in sustainable micro irrigation, with the goal of increasing crop yield and quality and conserving water.